Targeting immune response with therapeutic vaccines in premalignant lesions and cervical cancer: hope or reality from clinical studies. (2nd October 2016) - Vici, P; Pizzuti, L; Mariani, L; Zampa, G; Santini, D; Di Lauro, L; Gamucci, T; Natoli, C; Marchetti, P; Barba, M; Maugeri-Saccà, M; Sergi, D; et al.
ABSTRACT: Human papillomavirus (HPV) is widely known as a cause of cervical cancer (CC) and cervical intraepithelial neoplasia (CIN). HPVs related to cancer express two main oncogenes, i.e. E6 and E7, considered as tumorigenic genes; their integration into the host genome results in the abnormal regulation of cell cycle control. Due to their peculiarities, these oncogenes represent an excellent target for cancer immunotherapy. In this work the authors highlight the potential use of therapeutic vaccines as safe and effective pharmacological tools in cervical disease, focusing on vaccines that have reached the clinical trial phase. Many therapeutic HPV vaccines have been tested in clinical trials with promising results. Adoptive T-cell therapy showed clinical activity in a phase II trial involving advanced CC patients. A phase II randomized trial showed clinical activity of a nucleic acid-based vaccine in HPV16 or HPV18 positive CIN. Several trials involving peptide-protein-based vaccines and live-vector based vaccines demonstrated that these approaches are effective in CIN as well as in advanced CC patients. HPV therapeutic vaccines must be regarded as a therapeutic option in cervical disease. The synergic combination of HPV therapeutic vaccines with radiotherapy, chemotherapy, immunomodulators or immune checkpoint inhibitors opens a new and interesting scenario in this disease.